Internationalization Strategies of German Universities - Bremer, Ulrich (Schriftenreihe der HHL Leipzig Graduate School of Management, 2018)
Ulrich Bremer examines the internationalization process of German public research universities, extracts multiple expected factors of impact from existing theory, tests them against data and thus delivers implications for research and practice. Strategy-based international partnerships, specialization and university size represent most relevant factors. The complex interplay of strategy and leadership are shown, a framework for their assessment is provided and conclusions in the fields of digitalization, uncontrolled migration and growing nationalism are drawn. Contents Exploring the Impact of Influencing Factors on Internationalization, Using Quantitative Methods Exploring Internationalization Approaches for the Future, Using Qualitative Methods Role of Leadership in the Internationalization Process of German Universities Purpose-Based Leadership in German Universities Target Groups Researchers and students in the field of economics with focus on internalization Executives of German public research universities The Author Dr. Ulrich Bremer completed his doctoral study under the supervision of Prof. Dr. Andreas Pinkwart at HHL Leipzig Graduate School of Management. He is managing director at DIU Dresden International University.